E-research untuk Universitas Riset Studi Kasus Layanan Digital Perpustakaan Universitas Sumatera Utara - Himma Dewiyana; Lely Emiliyana; Muhammad Salim; Mas Irwansyah Putra (Institut Agama Islam Negeri Salatiga, 2022)
This study aims to determine e-research on the Digital Service Library of Universitas Sumatera Utara in supporting the mission of Universitas Sumatera Utara as a research university. This study uses a qualitative method with a descriptive approach. Research informants are users of Digital Services, namely Lecturers and Postgraduate Students who are conducting research. Informants were taken using snowball sampling. During the data collection process, eleven key informants were netted, namely six lecturers, five postgraduate students. One additional informant is the Digital Service Librarian. The results showed that e-research at the Digital Service Library of Universitas Sumatera Utara was first, information retrieval, namely the assistance provided by librarians to users in finding references relevant to the research topic. Second, e-resources, namely electronic information sources: e-repository, e-journal, e-thesis, and e-dissertation. Third, information literacy, namely training on the use of online databases, e-journal and e-book searches. Fourth, global network, namely internet facilities with bandwidth 30 Mbps and wifi for library users who are doing research. The conclusion that can be drawn is that e-research in the Digital Services Library of Universitas Sumatera Utara has supported the mission of Universitas Sumatera Utara as a research university. Digital Services has acted as a mediator and facilitator in research activities at Universitas Sumatera Utara. The facilities in Digital Services are used to build research excellence and maintain the status of Universitas Sumatera Utara as a global research university.